Balance of payments crises under fixed exchange rate in Colombia: 1938-1967 (2006)
Between 1938 and 1967, including the Bretton Woods period after 1947, Colombia pegged its currency to the dollar. Although the exchange rate was fixed, the peso was devaluated more than 12% on six occasions. The devaluation episodes were complex, traumatic, highly politicized and had costly macroeconomic effects. The Bretton Woods agreement stated that countries could only devalue their exchange rate in the presence of fundamental imbalances driven, for example, by structural terms of trade deterioration. However, this paper states that in Colombia, the imbalance in the money market was a key factor in explaining the exchange rate crises during the period. The paper is organized as follows: first, a simple theoretical model of a small open economy with imperfect capital mobility is described in order to examine the possible causes of nominal devaluations; second, a narrative approach is used to describe the economic circumstances that surrounded each of the devaluation episodes; finally, a set of econometric tests are used in order to identify the key variables behind the macroeconomic imbalances that preceded each exchange rate crisis. The results show that the external imbalances were mainly associated with the imbalances in the money market. Terms of trade deterioration account for just a small part of current account crises.